The endocytosis gene END3 is essential for the glucose-induced rapid decline of small vesicles in the extracellular fraction in Saccharomyces cerevisiae - Giardina, Bennett J. (Co-Action Publishing, 2014)
BACKGROUND: Protein secretion is a fundamental process in all living cells. Gluconeogenic enzymes are secreted when Saccharomyces cerevisiae are grown in media containing low glucose. However, when cells are transferred to media containing high glucose, they are internalized. We investigated whether or not gluconeogenic enzymes were associated with extracellular vesicles in glucose-starved cells. We also examined the role that the endocytosis gene END3 plays in the internalization of extracellular proteins/vesicles in response to glucose addition. METHODS: Transmission electron microscopy was performed to determine the presence of extracellular vesicles in glucose-starved wild-type cells and the dynamics of vesicle transport in cells lacking the END3 gene. Proteomics was used to identify extracellular proteins that associated with these vesicles. RESULTS: Total extracts prepared from glucose-starved cells consisted of about 95% small vesicles (30–50 nm) and 5% large structures (100–300 nm). The addition of glucose caused a rapid decline in small extracellular vesicles in wild-type cells. However, most of the extracellular vesicles were still observed in cells lacking the END3 gene following glucose replenishment. Proteomics was used to identify 72 extracellular proteins that may be associated with these vesicles. Gluconeogenic enzymes fructose-1,6-bisphosphatase, malate dehydrogenase, isocitrate lyase, and phosphoenolpyruvate carboxykinase, as well as non-gluconeogenic enzymes glyceraldehyde-3-phosphate dehydrogenase and cyclophilin A, were distributed in the vesicle-enriched fraction in total extracts prepared from cells grown in low glucose. Distribution of these proteins in the vesicle-enriched fraction required the integrity of the membranes. When glucose was added to glucose-starved wild-type cells, levels of extracellular fructose-1,6-bisphosphatase, malate dehydrogenase, isocitrate lyase, phosphoenolpyruvate carboxykinase, glyceraldehyde-3-phosphate dehydrogenase, and cyclophilin A were reduced. In contrast, in cells lacking the END3 gene, levels of these proteins in the extracellular fraction remained high. CONCLUSION: The END3 gene is required for the rapid decline of extracellular proteins and vesicles in response to glucose addition.